Genetic differentiation among natural populations of the lizard complex Darevskia raddei as inferred from genome microsatellite marking - Omelchenko, A. V.; Girnyk, A. E.; Osipov, F. A.; Vergun, A. A.; Petrosyan, V. G.; Danielyan, F. D.; Arakelyan, M. S.; Ryskov, A. P. (Russian journal of genetics, 2016)
The article presents the genetic parameters of the populations of lizards of the Darevskia raddei complex (D. raddei nairensis and D. raddei raddei) and the populations of D. valentini calculated on the basis of the analysis of variability of 50 allelic variants of the three nuclear genome microsatellite-containing loci of 83 individuals. It was demonstrated that the F ₛₜ genetic distances between the populations of D. raddei nairensis and D. raddei raddei were not statistically significantly different from the F ₛₜ genetic distances between the populations of different species, D. raddei and D. valentini. At the same time, these distances were statistically significantly higher than the F ₛₜ distances between the populations belonging to one species within the genus Darevskia. These data suggest deep divergence between the populations of D. raddei raddei and D. raddei nairensis of the D. raddei complex and there arises the question on considering them as separate species.